Early Healing Events around Titanium Implant Devices with Different Surface Microtopography: A Pilot Study in an In Vivo Rabbit Model - Ester Orsini; Stefano Salgarello; Désirée Martini; Beatrice Bacchelli; Marilisa Quaranta; Luciano Pisoni; Emma Bellei; Monika Joechler; Vittoria Ottani (The Scientific World Journal)
In the present pilot study, the authors morphologically investigated sandblasted, acid-etched surfaces (SLA) at very early experimental times. The tested devices were titanium plate-like implants with flattened wide lateral sides and jagged narrow sides. Because of these implant shape and placement site, the device gained a firm mechanical stability but the largest portion of the implant surface lacked direct contact with host bone and faced a wide peri-implant space rich in marrow tissue, intentionally created in order to study the interfacial interaction between metal surface and biological microenvironment. The insertion of titanium devices into the proximal tibia elicited a sequence of healing events. Newly formed bone proceeded through an early distance osteogenesis, common to both surfaces, and a delayed contact osteogenesis which seemed to follow different patterns at the two surfaces. In fact, SLA devices showed a more osteoconductive behavior retaining a less dense blood clot, which might be earlier and more easily replaced, and leading to a surface-conditioning layer which promotes osteogenic cell differentiation and appositional new bone deposition at the titanium surface. This model system is expected to provide a starting point for further investigations which clarify the early cellular and biomolecular events occurring at the metal surface.